The influence of conservation awareness and climate change perception on consumer rice waste behavior—empirical evidence from a survey of Tokyo consumers in Japan - Li, Caixia; Liu, Zengjin; Zhou, Zhou (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood waste not only affects global food security but also poses challenges to environmental sustainability and socioeconomic development. As one of the major food-consuming countries, Japan faces a significant issue of rice waste, warranting particular attention.MethodsThis study utilizes survey data from 500 Tokyo consumers and applies a multinomial ordered logistic regression model (also known as the proportional odds model, which requires the proportional odds assumption to be satisfied through a parallelism test) to analyze the key factors influencing rice waste behavior.ResultsThe results indicate that conservation awareness and climate change perception positively affect waste behavior at the 1% significance level, while their interaction term positively influences waste behavior at the 10% significance level, suggesting that climate change perception moderates the impact of conservation awareness on waste behavior. Government guidance has a positive effect on waste behavior at the 5% significance level, whereas environmental awareness negatively affects waste behavior at the 10% significance level. However, factors such as food education, price range, purchase frequency, perception and expectation of rice shortages, willingness to adjust diet, gender, age, education level, occupation, and household monthly income do not exhibit significant effects. Additionally, the study finds that households with more members tend to waste more rice, while consumers with a stronger awareness of climate change impacts are likelier to reduce waste.DiscussionThese findings provide valuable policy insights for food waste management in Japan and other developed countries. Governments can promote a culture of conservation, enhance public awareness of climate change, and improve food security policies to foster more sustainable food consumption patterns.